Probing protein stability: towards a computational atomistic, reliable, affordable, and improvable model - Nobili, Germano; Botticelli, Simone; La Penna, Giovanni; Morante, Silvia; Rossi, Giancarlo; Salina, Gaetano (Frontiers in Molecular Biosciences, 2023)
We present an improved application of a recently proposed computational method designed to evaluate the change of free energy as a function of the average value of a suitably chosen collective variable in proteins. The method is based on a full atomistic description of the protein and its environment. The goal is to understand how the protein melting temperature changes upon single-point mutations, because the sign of the temperature variation will allow us to discriminate stabilizing vs.\ destabilizing mutations in protein sequences. In this refined application the method is based on altruistic {well-tempered} metadynamics, a variant of multiple-walkers metadynamics. The obtained metastatistics is then modulated by the maximal constrained entropy principle. The latter turns out to be especially helpful in free-energy calculations as it is able to alleviate the severe limitations of well-tempered metadynamics in properly sampling folded and unfolded configurations. In this work we apply the computational strategy outlined above in the case of the bovine pancreatic trypsin inhibitor, a well-studied small protein that is a reference for computer simulations since decades. We compute the variation of the melting temperature characterizing the folding-unfolding process between the wild-type protein and two of its single-point mutations that are seen to have opposite effect on the free energy changes. The same approach is used for free energy difference calculations between a truncated form of frataxin and a set of five of its variants. Simulation data are compared to {\em in vitro} experiments. In all cases the sign of the change of melting temperature is reproduced, under the further approximation of using an empirical effective mean-field to average out protein-solvent interactions.